Eau Claire Basket Investment Track: A Seven Year Comparison of the Performance of Local Stocks - Przybelski, Chaid; Tsogtbaatar, Enkhjavkhlan; Streeter, Ben; Schmitt, Jeremy; Porwoll, Matt (My University, 2012)
The Chippewa Valley Center for Economic Research and Development (CVCERD) collects and maintains a variety of stock market and investment data. In particular, the CVCERD tracks the annual stock performance for a list of publicly-owned companies that are of local/regional interest through a simple investment basket called the Eau Claire Area Stock Basket (ECB). This study presents an annual comparison of the performance of the ECB between 2005 and the first quarter of 2012. This time period is of interest because it begins a few years prior to the great recession and financial collapse and continues through the subsequent economic recovery to the present.
Color poster with text, graphs, and tables.
Keywords: Posters; Investments--Wisconsin--Eau Claire; Eau Claire Area Stock Basket (Wis.); Stock--Charts, diagrams, etc.; Stocks--Wisconsin--Eau Claire